Astounding optical illusions - Joyce, Katherine (New York : Sterling Pub. Co., 1994)
Presents a collection of fantastic optical illusions including designs, hidden pictures, shadow illusions, and magic
Includes index.
Keywords: Optical illusions -- Juvenile literature; Optical illusions; Perception